La Guerra de la Independencia como guerra religiosa: el ejemplo de los sitios de Zaragoza y Gerona - Genís Barnosell (Nuevo mundo - Mundos Nuevos, 2010)
The Spanish War of Independence or Peninsular War (1808-14) had an undeniable religious side. Some facts of the war were interpreted from biblical passages like the first and second book of Maccabees. As a result, the war became a struggle between Good and Evil, and probably one of the signs of the approaching end of time. The result was a fight like the uncompromising defence of the sieges of Gerona and Zaragoza.